Superior Mesenteric Artery Syndrome—Believe in it! Report of a Case - Sante Capitano; Gianfranco Donatelli; Gianfranco Boccoli (Case Reports in Surgery)
We present a case of a man with amyotrophic lateral sclerosis who developed superior mesenteric artery syndrome (SMAS) following the confection of feeding jejunostomy. He was successfully managed by conservative treatment. Left lateral positioning during enteral feeding allowed quick resolution of the occlusive state. Various surgical interventions have been associated with SMAS, directly or indirectly, by reducing the width of the aortomesenteric angle. The operative stress was probably what triggered symptomatology in our patient thus to conclude that the surgical stress should be considered as a causal factor triggering the SMAS in a context of other predisposing factors.